2007
DOI: 10.1111/j.1937-5956.2007.tb00283.x
|View full text |Cite
|
Sign up to set email alerts
|

A Field Study of RFID Deployment and Return Expectations

Abstract: Radio Frequency Identification (RFID) technology promises to transform supply chain management. Building on previous research in information systems and supply chain management, this paper proposes a theoretical framework for RFID adoption and benefits, and tests the framework using data on u. s. firms. Our analysis suggests that there is a positive association between information technology (IT) application deployment and RFID adoption. We find that RFID implementation spending and partner mandate are associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(94 citation statements)
references
References 98 publications
(142 reference statements)
3
90
0
1
Order By: Relevance
“…Indeed, recent empirical findings in the production and logistics environment showed that the lack of technical knowledge on RFID within firms (specially SMEs) is one of the major barriers to successful RFID implementation (Myerson, 2006;Huber et al, 2007;Whitaker et al 2007). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recent empirical findings in the production and logistics environment showed that the lack of technical knowledge on RFID within firms (specially SMEs) is one of the major barriers to successful RFID implementation (Myerson, 2006;Huber et al, 2007;Whitaker et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…However, RFID is considered as a disruptive innovation Vail & Agarwal, 2007), since it is thought to radically change interdependent supply chain processes and practices Bardaki et al, 2007;Curtin et al, 2007;Whitaker et al, 2007;Chuang & Shaw, 2008).…”
Section: Rfid Benefitsmentioning
confidence: 99%
“…There will continue to be a need for studies that enrich understanding by pointing to associations (Bharadwaj 2000;Mithas et al 2007Ramasubbu et al 2008;Ray et al 2004Ray et al , 2005Whitaker et al 2007) or the nested nature of relationships (Ang et al 2002, Mithas et al 2006) that can subsequently be tested using the counterfactual framework we discussed herein. Likewise, there is always a need for detailed case studies and historical accounts that help identify relevant variables to understand an unfolding phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and sanitary characterization is the first step to building a detailed and useful information package; however, it is also essential to define all the other relevant input and output factors in order to trace plants and relative products. Traceability may lead to technical difficulties requiring additional efforts to ensure a trouble-free processing of the material flow (Whitaker et al 2007). In any case, the need of trouble-free processing for plants and foods is a requisite in many countries, even if traceability is not standardized.…”
Section: Economic Sustainabilitymentioning
confidence: 99%